Carbohydrate quality changes and concurrent changes in cardiovascular risk factors: a longitudinal analysis in the PREDIMED-Plus randomized trial. Issue 2 (23rd December 2019) - Martínez-González, Miguel A; Fernandez-Lazaro, Cesar I; Toledo, Estefanía; Díaz-López, Andrés; Corella, Dolores; Goday, Albert; Romaguera, Dora; Vioque, Jesús; Alonso-Gómez, Ángel M; Wärnberg, Julia; Martínez, J Alfredo; Serra-Majem, Luís; et al.
ABSTRACT: Background: Overall quality of dietary carbohydrate intake rather than total carbohydrate intake may determine the risk of cardiovascular disease (CVD). Objective: We examined 6- and 12-mo changes in carbohydrate quality index (CQI) and concurrent changes in several CVD risk factors in a multicenter, randomized, primary-prevention trial (PREDIMED-Plus) based on an intensive weight-loss lifestyle intervention program. Methods: Prospective analysis of 5373 overweight/obese Spanish adults (aged 55–75 y) with metabolic syndrome (MetS). Dietary intake information obtained from a validated 143-item semiquantitative food-frequency questionnaire was used to calculate 6- and 12-mo changes in CQI (categorized in quintiles), based on 4 criteria (total dietary fiber intake, glycemic index, whole grain/total grain ratio, and solid carbohydrate/total carbohydrate ratio). The outcomes were changes in intermediate markers of CVD. Results: During the 12-mo follow-up, the majority of participants improved their CQI by increasing their consumption of fruits, vegetables, legumes, fish, and nuts and decreasing their consumption of refined cereals, added sugars, and sugar-sweetened beverages. After 6 mo, body weight, waist circumference (WC), systolic and diastolic blood pressure (BP), fasting blood glucose, glycated hemoglobin (HbA1c), triglyceride levels, triglycerides and glucose (TyG) index, and TyG-WC decreased across successive quintiles of improvement in the CQI. After 12 mo, improvements were additionally observed for HDL cholesterol and for the ratio of total to HDL cholesterol. Favorable improvements (expressed in common units of SD and 95% CI) for quintile 5 compared with quintile 1 of CQI change were observed for most risk factors, including TyG-WC (SD −0.20; 95% CI −0.26, −0.15), HbA1c (SD −0.16; 95% CI −0.23, −0.10), weight (SD −0.12; 95% CI −0.14, −0.09), systolic BP (SD −0.11; 95% CI −0.19, −0.02) and diastolic BP (SD −0.11; 95% CI −0.19, −0.04). Conclusions: Improvements in CQI were strongly associated with concurrent favorable CVD risk factor changes maintained over time in overweight/obese adults with MetS. This trial was registered as ISRCTN 89898870.